Visual Cortical Processing in Children with Early Bilateral Cochlear Implants: A VEP Analysis - Ola Badarni-Zahalka; Ornella Dakwar-Kawar; Cahtia Adelman; Salma Khoury-Shoufani; Josef Attias (Children)
Background/Objectives: Cochlear implantation is the primary treatment for severe-to-profound hearing loss, yet outcomes vary significantly among recipients. While visual–auditory cross-modal reorganization has been identified as a contributing factor to this variability, its impact in early-implanted children remains unclear. To address this knowledge gap, we investigated visual processing and its relationship with auditory outcomes in children who received early bilateral cochlear implants. Methods: To examine potential cross-modal reorganization, we recorded visual evoked potentials (VEPs) in response to pattern-reversal stimuli in 25 children with cochlear implants (CIs) (mean implantation age: 1.44 years) and 28 age-matched normal-hearing (NH) controls. Analysis focused on both the occipital region of interest (ROI: O1, OZ, and O2 electrode sites) and right temporal ROI, examining VEP components and their correlation with speech perception outcomes. Results: Unlike previous studies in later-implanted children, the overall occipital ROI showed no significant differences between groups. However, the left occipital electrode (O1) revealed reduced P1 amplitudes and delayed N1 latencies in CI users. Importantly, O1 N1 latency negatively correlated with speech-in-noise performance (r = −0.318; p = 0.02). The right temporal region showed no significant differences in VEP N1 between groups and no correlation with speech performance in CI users. Conclusions: Early bilateral cochlear implantation appears to preserve global visual processing, suggesting minimal maladaptive reorganization. However, subtle alterations in left occipital visual processing may influence auditory outcomes, highlighting the importance of early intervention and the complex nature of sensory integration in this population.